Augmented Reality in Mathematics Education: A Bibliometric Analysis Utilizing the Scopus Database - Edi Supriyadi; Dadang Juandi; Turmudi Turmudi; Aneu Pebrianti (Departemen Pendidikan Matematika, FPMIPA, UPI, 2023)
Augmented reality (AR) is a technology that combines real and virtual elements to create a hybrid experience. Research has shown that AR can improve spatial abilities, assist learning, and increase motivation in students. It has also been demonstrated to facilitate collaborative learning and the evolution of learning in mathematics. The purpose of this study is to analyze the status and trends of AR research in mathematics education over the past 20 years. AR has been studied extensively and has many potentials uses in education and learning, but it may be used more frequently in certain situations or for specific goals. The study used Scopus and PRISMA to conduct a systematic review of articles and Biblioshiny software for bibliometric analysis, including co-citation and co-author analysis. The research on augmented reality in mathematics education has grown steadily over the past 20 years and has had a significant impact, with an average of 13.74 citations per document. It has also been conducted and disseminated internationally and has seen a recent increase in publications. The most relevant source for this research is